2022
DOI: 10.1007/s10742-021-00266-4
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating respondent-driven sampling into web-based discrete choice experiments: preferences for COVID-19 mitigation measures

Abstract: To slow the spread of COVID-19, most countries implemented stay-at-home orders, social distancing, and other nonpharmaceutical mitigation strategies. To understand individual preferences for mitigation strategies, we piloted a web-based Respondent Driven Sampling (RDS) approach to recruit participants from four universities in three countries to complete a computer-based Discrete Choice Experiment (DCE). Use of these methods, in combination, can serve to increase the external validity of a study by enabling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We identified a further four studies published after the review searches were undertaken (Albani et al 2021, Bourdeaux et al 2021, Homaie Rad et al 2021, Johnson et al 2022). Alongside the five studies identified from reviews, a total of nine primary studies are included in this report.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified a further four studies published after the review searches were undertaken (Albani et al 2021, Bourdeaux et al 2021, Homaie Rad et al 2021, Johnson et al 2022). Alongside the five studies identified from reviews, a total of nine primary studies are included in this report.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson et al (2022) and Homaie Rad et al (2021) undertook discrete choice experiments (DCEs) to elicit public preferences regarding COVID-19 in the United States of America and Iran, respectively. Johnson et al (2022) undertook their DCE across universities in the USA, Mexico and Kenya to try to represent an income spread in their findings. Respondents reported a preference to receive financial government compensation during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the evidence for the employment of RDS to recruit PWID or HIV+ groups during the pandemic is lacking, there is increasing evidence of successful use of RDS to recruit hard-to-reach populations beyond those described in this study. For example, Jonhson et al resorted to RDS to recruit a sample of isolated college students in China to document their views on mitigation measures ( 37 ). Another study by Mukhergee et al explored patterns of media consumption during a COVID-19 lockdown in India using a large RDS-recruited sample ( 38 ).…”
Section: Discussionmentioning
confidence: 99%